Tra I Libri Di Isacco Argiro. - Gioffreda, Anna. (Transmissions Series, 2020)
Transmissions aims to constitute a space for documentation, theoretical and methodological reflection and critical discussion on the transmission of texts. The focus is on textual production in Greek and Latin, while remaining open to comparisons with the dynamics of transmission in the graphic and textual production of other cultures and languages. In doing so, the series leads towards a phenomenology and theory of the processes of transmission.